Laser ablation resistant polymer-based protective coating and preparation method thereof
By using a polysilica alkyl coating with a combination of multi-nano phase in the anti-laser ablation coating, combined with spin coating method and ultrasonic dispersion technology, the problem of single coating function and thermal damage is solved, and high-performance lasers are achieved Protective effect.
Patent Information
- Application Number
- CN202411272741.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-27
AI Technical Summary
The existing anti-laser ablation coating has a single function, and it is difficult to take into account both mechanical properties, tribological properties and wave absorption properties. Cracks and pores are prone to occur during the curing process. Most preparation methods have a large thermal damage to the matrix and are not suitable for precision equipment. protection.
Using polysiliazolamyl protective coating, the nanoparticles include TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes. The coating is formed on the substrate surface by spin coating, and the multiphase combination and ultrasonic dispersion of nanoparticles are used. Technology improves the mechanical properties and thermal insulation properties of the coating.
It significantly improves the mechanical properties and comprehensive properties of the coating, enhances the protection ability of laser ablation, reduces the internal defects of the coating, and is suitable for the protection of precision equipment.
Smart Images

Figure CN119193000A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser protection, and in particular relates to a polymer-based protective coating resistant to laser ablation and a preparation method thereof. Background Art
[0002] Ablation-resistant coating is one of the most widely studied anti-laser coatings. Its protection mechanism is that the coating material undergoes endothermic reactions such as cracking and gasification under the action of laser, while consuming a large amount of laser energy, which greatly reduces the heat transferred to the substrate, thereby achieving the purpose of protection. Polysilazane precursor refers to a polymer whose main chain is composed of -Si-N- units. Under certain conditions, they are converted into Si3N4, SiCN and SiON ceramics through reactions such as dehydrogenation and condensation. While consuming laser energy, it can generate a high-temperature resistant ceramic phase, which is an ideal raw material for anti-laser ablation coating.
[0003] The Chinese invention patent with publication number CN101445702A discloses a protective coating resistant to laser ablation and a preparation method thereof. The method is characterized in that polycarbosilane and divinylbenzene are first mixed in proportion, heated and stirred to form a transparent mixed solution, and then an appropriate amount of chopped carbon fiber and zirconium oxide powder are added to the mixed solution and stirred evenly to obtain a coating with a certain viscosity, and the coating is applied to the surface of the pretreated aluminum alloy substrate and placed in an oven for heating and curing treatment. After curing, it is cooled to room temperature to obtain a composite coating. This coating can reduce or eliminate the impact of the laser on the substrate to a certain extent, thereby playing a role in laser protection. However, although this method can absorb laser energy to a certain extent, during the laser irradiation process, the pores and cracks caused by the thermal expansion of the coating are relatively serious, and the function is relatively single.
[0004] The Chinese invention patent with publication number CN109705674A discloses a polyvinyl butyral resin-based laser protection coating and its preparation method. The base of the coating is polyvinyl butyral resin and the filler is (Sn1-x-ySbxEry)O2. The coating is effective for 1.06μm
[0005] It has dual functions of absorption and up-conversion for 1.54μm infrared lasers, and has strong absorption effect for 10.6μm infrared lasers, which can achieve the purpose of laser protection; it can withstand temperature changes in the range of -40℃ to 350℃, and the diffuse reflectivity of the coating is kept below 0.5%; it can be cured at room temperature, and has the advantages of thin thickness, uniform thickness, good surface condition, adhesion ≥1 level, and impact strength ≥50kg·cm, so it can be used in the field of laser protection as a coating that can withstand both high and low temperatures. However, compared with polysilazane-based coatings, this coating absorbs less energy and has poor thermal insulation performance.
[0006] The Chinese invention patent with the publication number CN111500146A discloses a composite laser ablation resistant coating, which includes the following components: phenolic resin, zirconium oxide, physical filler, solvent, dispersant, defoamer, leveling agent, and the preparation method thereof is to first dilute the phenolic resin with part of the solvent to form a resin slurry; then stir the resin slurry, dispersant, defoamer, leveling agent and the remaining solvent at a low speed; then add zirconium oxide and physical filler and stir at a high speed to obtain the laser ablation resistant coating, and use the slow gradient heating and drying technology to obtain the laser ablation resistant coating. In the coating of the present invention, the phenolic resin is a binder, and the zirconium oxide is a phase change material. The zirconium oxide has three crystal forms under normal pressure. When it is irradiated by a high-energy laser, it will generate instantaneous high-energy heat, thereby causing the crystal form to change. The occurrence of the phase change effect leads to an increase in the reflectivity of the coating surface, which relatively reduces the irradiation heat energy of the laser, thereby ensuring that the coating produces an anti-high-energy laser ablation effect. However, this coating relies solely on the heat-insulating ability of zirconium oxide to resist laser ablation, and consumes less laser energy than polymer-based coatings.
[0007] Therefore, the existing ablative coatings have the following technical problems:
[0008] 1. Only a single ceramic precursor material is used to protect the aircraft surface, which has a single function and poor coating quality. It is impossible to take into account the mechanical properties, tribological properties and wave absorption properties of the coating.
[0009] 2. Single precursor polymer coating, the formation of cracks and pores during the solidification process, limits the maximum coating thickness to a few microns.
[0010] 3. Most coating preparation methods, such as plasma spraying and thermal sintering, cause significant thermal damage to the substrate and are not suitable for the protection of small precision equipment such as aircraft surfaces. Summary of the invention
[0011] The present invention aims to solve at least one of the technical problems existing in the prior art and to provide a new technical solution for a polymer-based protective coating resistant to laser ablation and a method for preparing the same.
[0012] According to a first aspect of the present invention, there is provided a polymer-based protective coating resistant to laser ablation, wherein the coating covers the surface of a protected substrate; the coating comprises a precursor solution and nanoparticles, wherein the nanoparticles comprise TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes, and the mass ratio of TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes is 2-5:1-3:1-2:1-3:2-3:1-1.5:1-1.5, and in the coating, the mass percentage of the nanoparticles is 10%-25%, and the mass percentage of the precursor solution is 75%-90%.
[0013] Optionally, a spin coating method is used to form a protective coating on the surface of the protected substrate.
[0014] According to a second aspect of the present invention, a method for preparing a polymer protective coating resistant to laser ablation is provided, comprising the following steps:
[0015] Step S100, pre-treating the substrate;
[0016] Step S200, preparing a precursor solution; wherein the precursor solution includes polysilazane and xylene solvent;
[0017] Step S300, TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles are added to the precursor solution in sequence, stirred evenly, and then placed in an ultrasonic disperser for ultrasonic dispersion for 5-15 minutes, and then a defoamer with a mass fraction of 0.3%-1.2% is added, and stirring is continued in an electromagnetic stirrer for 5-15 minutes to form a uniform mixed solution;
[0018] Wherein, in the mixed solution, the mass ratio of TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles is 2-5:1-3:1-2:1-3:2-3:1-1.5:1-1.5, and the mass percentage of nanoparticles is 10%-25%, and the mass percentage of the precursor solution is 75%-90%;
[0019] Step S400, coating the pretreated substrate with the mixed solution by spin coating, and curing the mixed solution in an Ar atmosphere to form a coating on the surface of the substrate.
[0020] Optionally, preparing a precursor solution comprises:
[0021] The polysilazane is dissolved in a xylene solvent to obtain a precursor solution, and an electric stirrer is used for stirring at a stirring speed of 1500 r / min-2500 r / min and a stirring time of 5-10 min; wherein the mass percentage of the polysilazane in the precursor solution is 40%-60%.
[0022] Optionally, the substrate is pretreated, including:
[0023] The surface and edges of the substrate were smoothed with sandpaper and then ultrasonically cleaned in alcohol.
[0024] Optionally, the material of the substrate is carbon or carbon composite material, or the material of the substrate is metal; the sandpaper is sandpaper with a mesh size less than 100; the temperature of ultrasonic cleaning is 25° C.-30° C., and the cleaning time is 5-10 min.
[0025] Optionally, in step S300, after TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles are sequentially added to the precursor solution, the precursor solution is stirred with an electric stirrer at a stirring speed of 1500r / min-2000r / min and a stirring time of 2-5min.
[0026] Optionally, the particle sizes of the TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotube particles are all 300nm-1000nm.
[0027] Optionally, when the coating is performed by spin coating, the rotation speed is 2000 r / min-2500 r / min, and the time is 30 s-40 s.
[0028] Optionally, when curing is performed in an Ar atmosphere, the curing conditions are as follows:
[0029] The temperature was first raised to 230°C at a heating rate of 2°C / min and kept at this temperature for 2h, and then cooled to 25°C at a cooling rate of 3°C / min and kept at this temperature for 30min.
[0030] A technical effect of the present invention is:
[0031] In the embodiment of the present application, nano B4C and carbon nanotubes are used to prepare an anti-laser ablation protective coating, wherein the passivation effect of nano B4C and the pinning effect of carbon nanotubes can greatly improve the mechanical properties of the coating. Therefore, the mechanical properties and bonding strength of the polysilazane anti-laser ablation coating are improved by adjusting the content of nano B4C and carbon nanotubes.
[0032] At the same time, the multi-nanophase Al and VO2 reflect laser, polysilazane consumes laser energy, the cracking product SiCN is heat-insulating, nano-cBN is wear-resistant, and nano-TiO2 and SiC absorb waves, which work together to effectively improve the comprehensive performance of the coating and provide effective protection for the substrate.
[0033] Furthermore, during the laser ablation process, TiO2, Al, and B4C in the coating react to generate Al2O3, TiB2, and TiC. Among them, TiB2 has a very high hardness. The oxidation resistance temperature of TiB2 in air can reach 1000°C, and TiC has the characteristics of good thermal stability, which further improves the performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a chemical reaction formula of the nanophase particles during laser irradiation according to an embodiment of the present invention;
[0035] Figure 2 is the structural formula of polysilazane according to one embodiment of the present invention;
[0036] Figure 3 A schematic structural diagram of a polymer-based protective coating resistant to laser ablation according to an embodiment of the present invention;
[0037] Figure 4 A schematic flow chart of a method for preparing a polymer-based protective coating resistant to laser ablation according to an embodiment of the present invention;
[0038] Figure 5 A schematic flow chart of a method for preparing a laser ablation resistant polymer-based protective coating according to another embodiment of the present invention;
[0039] Figure 6 The figure is a surface schematic diagram of a laser ablation resistant polymer-based protective coating according to an embodiment of the present invention.
[0040] In the figure: 1. substrate; 2. coating; 3. high-energy laser emitter. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present application.
[0042] The embodiments of the present application will be described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0043] The term "first" or "second" in the specification and claims of this application may include one or more of the features explicitly or implicitly. In the description of this application, unless otherwise specified, "plurality" means two or more. In addition, "and / or" in the specification and claims means at least one of the connected objects, and the character " / " generally means that the objects connected before and after are in an "or" relationship.
[0044] According to a first aspect of the present invention, a polymer-based protective coating resistant to laser ablation is provided, which is suitable for preparing a protective coating resistant to laser ablation on the surface of an aircraft such as a drone or a small aircraft. Figure 3When the high-energy laser beam emitted by the high-energy laser emitter 3 acts on the protective coating 2 on the surface of the substrate 1, the protective coating 2 can effectively protect the substrate 1 due to the uniform distribution of nanoparticles inside the protective coating 2.
[0045] Specifically, the laser ablation-resistant polymer-based protective coating includes a precursor solution (ie, polymer polysilazane) and multiphase nanoparticles. It is reasonably designed and has the advantages of high laser energy reflectivity, good heat insulation effect, and outstanding mechanical properties.
[0046] More specifically, the protective coating 2 covers the surface of the protected substrate 1; wherein the multiphase nanoparticles include TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes, the mass ratio of TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes is 2-5:1-3:1-2:1-3:2-3:1-1.5:1-1.5, and in the protective coating, the mass percentage of nanoparticles is 10%-25%, and the mass percentage of the precursor solution is 75%-90%. That is, the protective coating 2 is a polymer-based anti-laser ablation coating doped with multiphase nanoparticles.
[0047] It should be noted that the surface of the protective coating 2 is flat and smooth, and there are few internal structural defects, such as Figure 6 shown.
[0048] In the embodiment of the present application, nano B4C and carbon nanotubes are used to prepare an anti-laser ablation protective coating, wherein the passivation effect of nano B4C and the pinning effect of carbon nanotubes can greatly improve the mechanical properties of the coating. Therefore, the mechanical properties and bonding strength of the polysilazane anti-laser ablation coating are improved by adjusting the content of nano B4C and carbon nanotubes.
[0049] At the same time, the synergistic effects of multi-nanophase Al and VO2 reflecting laser, polysilazane consuming laser energy, cracking product SiCN insulating, nano-cBN wear-resistant, nano-TiO2 and SiC absorbing waves can effectively improve the comprehensive performance of the coating and provide effective protection for the substrate.
[0050] Further, during laser ablation, see Figure 1 , TiO2, Al, B4C in the coating react to form Al2O3, TiB2, TiC. Among them, TiB2 has a very high hardness. The oxidation resistance temperature of TiB2 in air can reach 1000℃, and TiC has the characteristics of good thermal stability, which further improves the performance of the coating.
[0051] In addition, after laser ablation at a power of 0.5KW to 1KW for 20 to 25 seconds, the laser-ablation-resistant polymer-based protective coating has no obvious ablation marks on the substrate surface, and can effectively protect the substrate.
[0052] Optionally, spin coating is used to form the coating on the surface of the protected substrate.
[0053] In the above-mentioned embodiment, the preparation method of the coating is relatively simple, which helps to obtain a coating with uniform thickness.
[0054] According to the second aspect of the present invention, see Figure 4 and Figure 5 , provides a method for preparing a polymer-based protective coating resistant to laser ablation, comprising the following steps:
[0055] Step S100, pre-treating the protected substrate.
[0056] Step S200, preparing a precursor solution; wherein the precursor solution comprises polysilazane and xylene solvent; see Figure 2 , Figure 2 It is the structural formula of polysilazane.
[0057] Step S300, TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles are added to the precursor solution in sequence, stirred evenly, and then placed in an ultrasonic disperser for ultrasonic dispersion for 5-15 minutes, and then a defoamer with a mass fraction of 0.3%-1.2% is added, and stirring is continued in an electromagnetic stirrer for 5-15 minutes to form a uniform mixed solution;
[0058] In the mixed solution, the mass ratio of TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotube particles is 2-5:1-3:1-2:1-3:2-3:1-1.5:1-1.5, the mass percentage of nanoparticles is 10%-25%, and the mass percentage of precursor solution is 75%-90%;
[0059] Step S400, coating the pretreated substrate with the mixed solution by spin coating, and curing the mixed solution in an Ar atmosphere to form a coating on the surface of the substrate.
[0060] In the above embodiment, the preparation method of the coating is relatively simple. Moreover, the anti-laser ablation protective coating prepared by the preparation method of the anti-laser ablation polymer-based protective coating has the following advantages:
[0061] 1. The coating is a polymer-based coating resistant to laser ablation. Through a specific material ratio, it has the following mechanism of action: carbon nanotubes and B4C play a pinning role on each phase in the coating, TiO2 and carbon nanotubes play a certain wave absorption role, and nano-cBN improves the hardness of the coating. After laser irradiation, Al and nano-VO2 are first used to reflect part of the laser energy, and then polysilazane is cracked to absorb part of the energy, and the ceramic coating generated by the cracking is used for heat insulation, and SiC and B4C are used in the coating to make up for the defects caused by thermal expansion.
[0062] 2. The ratio of each substance in the nano-doped phase is another key point of the present invention. According to the needs of the protective function, a suitable ratio is selected to give full play to the special properties of each phase.
[0063] 3. The key point of the process is sufficient ultrasonic dispersion to make the nanoparticles dispersed evenly in the organic precursor solution, improve the various properties of the coating in the form of dispersed distribution in the coating, and inhibit the aggregation, nucleation and growth of nanoparticles in the coating.
[0064] 4. The innovation of the present invention lies in that the prepared anti-laser ablation coating has high forming quality and excellent mechanical properties. After laser irradiation, the ceramic generation rate is high, the thermal insulation performance of the coating is further improved, and the anti-laser ablation performance of the coating can be improved.
[0065] Optionally, preparing a precursor solution comprises:
[0066] The polysilazane is dissolved in a xylene solvent to obtain a precursor solution, and an electric stirrer is used for stirring at a stirring speed of 1500 r / min-2500 r / min and a stirring time of 5-10 min; wherein the mass percentage of the polysilazane in the precursor solution is 40%-60%.
[0067] In the above-mentioned embodiment, the preparation method of the precursor solution is relatively simple, which helps the precursor solution to achieve the corresponding technical effect after the coating 2 is formed.
[0068] Optionally, the substrate is pretreated, including:
[0069] The surface and edges of the substrate were smoothed with sandpaper and then ultrasonically cleaned in alcohol.
[0070] In the above embodiment, it is helpful to prepare a coating 2 with uniform thickness on the surface of the substrate, and it is also helpful to ensure the bonding strength between the substrate 1 and the coating 2, thereby improving the service performance of the coating.
[0071] Optionally, the material of the substrate is carbon or carbon composite material, or the material of the substrate is metal; the sandpaper is sandpaper with a mesh size less than 100, which helps to smooth the surface of the substrate; the temperature of ultrasonic cleaning is 25°C-30°C, and the cleaning time is 5-10 minutes, which helps to ensure the cleaning effect of the substrate surface.
[0072] Optionally, in step S300, after TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles are sequentially added to the precursor solution, an electric stirrer is used to stir the precursor solution at a stirring speed of 1500 r / min-2000 r / min and a stirring time of 2-5 min.
[0073] In the above embodiment, the stirring method is relatively reasonable, which helps to ensure the uniformity of the mixed solution.
[0074] Optionally, the particle sizes of the TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotube particles are all 300nm-1000nm. This makes the particle size of each material more reasonable and helps to evenly distribute them in the mixed solution.
[0075] Optionally, when the coating is performed by spin coating, the rotation speed is 2000r / min-2500r / min and the time is 30s-40s. This makes the coating method more reasonable and helps to form a coating with uniform thickness.
[0076] Optionally, when curing is performed in an Ar atmosphere, the curing conditions are as follows:
[0077] First, the temperature was raised to 230°C at a heating rate of 2°C / min and kept at this temperature for 2 hours, and then cooled to 25°C at a cooling rate of 3°C / min and kept at this temperature for 30 minutes. This makes the curing method more reasonable and can ensure the curing effect of the coating.
[0078] Optionally, the thickness of the coating is 300 μm-600 μm, which makes the thickness of the coating reasonably designed, thereby better achieving the technical effect of the coating being resistant to laser ablation.
[0079] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A polymer-based protective coating resistant to laser ablation, characterized in that: The coating includes a precursor solution and nanoparticles, the nanoparticles include TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes, and the mass ratio of TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotubes is 2-5:1-3:1-2:1-3:2-3:1-1.5:1-1.5, and in the coating, the mass percentage of the nanoparticles is 10%-25%, and the mass percentage of the precursor solution is 75%-90%.
2. The laser ablation resistant polymer-based protective coating according to claim 1, characterized in that: The protective coating is formed on the surface of the protected substrate by spin coating.
3. A method for preparing a polymer-based protective coating resistant to laser ablation, characterized in that: The steps include: Step S100, pre-treating the protected substrate; Step S200, preparing a precursor solution; wherein the precursor solution includes polysilazane and xylene solvent; Step S300, TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles are added to the precursor solution in sequence, stirred evenly, and then placed in an ultrasonic disperser for ultrasonic dispersion for 5-15 minutes, and then a defoamer with a mass fraction of 0.3%-1.2% is added, and stirring is continued in an electromagnetic stirrer for 5-15 minutes to form a uniform mixed solution; In the mixed solution, the mass ratio of TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotube particles is 2-5:1-3:1-2:1-3:2-3:1-1.5:1-1.5, the mass percentage of nanoparticles is 10%-25%, and the mass percentage of precursor solution is 75%-90%; Step S400, coating the pretreated substrate with the mixed solution by spin coating, and curing the mixed solution in an Ar atmosphere to form a coating on the surface of the substrate.
4. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 3, characterized in that: Prepare a precursor solution, including: The polysilazane is dissolved in a xylene solvent to obtain a precursor solution, and an electric stirrer is used for stirring at a stirring speed of 1500 r / min-2500 r / min and a stirring time of 5-10 min; wherein the mass percentage of the polysilazane in the precursor solution is 40%-60%.
5. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 3, characterized in that: Pre-treat the substrate, including: The surface and edges of the substrate were smoothed with sandpaper and then ultrasonically cleaned in alcohol.
6. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 5, characterized in that: The material of the substrate is carbon or carbon composite material, or the material of the substrate is metal; the sandpaper is sandpaper with a mesh size less than 100; the temperature of ultrasonic cleaning is 25° C.-30° C., and the cleaning time is 5-10 min.
7. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 3, characterized in that: In step S300, after TiO2, Al, VO2, SiC, B4C, cBN, and carbon nanotube particles are sequentially added to the precursor solution, an electric stirrer is used to stir the precursor solution for 2-5 minutes.
8. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 3, characterized in that: The particle sizes of the TiO2, Al, VO2, SiC, B4C, cBN and carbon nanotube particles are all 300nm-1000nm.
9. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 3, characterized in that: When the coating is performed by spin coating, the rotation speed is 2000r / min-2500r / min and the time is 30s-40s.
10. The method for preparing a polymer-based protective coating resistant to laser ablation according to claim 3, characterized in that: When curing is carried out in an Ar atmosphere, the curing conditions are as follows: The temperature was first raised to 230°C at a heating rate of 2°C / min and kept at this temperature for 2h, and then cooled to 25°C at a cooling rate of 3°C / min and kept at this temperature for 30min.
Citation Information
Patent Citations
Method for preparing carbon / carbon-silicon carbide (C / C-SiC) composite self-sealing and anti-oxidation coating
CN101905979A
Cited By
Preparation method of carbon-containing refractory material
CN120309319A
Preparation method of anti-laser ablation coating based on C / C-SiC paper
CN121827136A
